Comparison of Inverse Distance Weighted and Natural Neighbor Interpolation Method at Air Temperature Data in Malang Region - Musashi, Jaka Pratama; Pramoedyo, Henny; Fitriani, Rahma (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2018)
The purpose of this study was to compare the results of Inverse Distance Weighted (IDW) and Natural Neighbor interpolation methods for spatial data of air temperature in the Malang Region. Interpolation is one way to determine a point of events from several points around the known value. Spatial interpolation can be used to estimate an area that does not have a data record using the value of its known surroundings. 38 points observation air temperature of Malang Region in 2016 is used as a sample point to interpolate the surrounding air temperature. Obtained optimum parameter power value is 2 for IDW interpolation method. The RMSE comparison results show that IDW method is better to be used than the Natural Neighbor Interpolation method with the RMSE values of 1,2292 for the IDW method and 1,6173 for the NN method.